2018
DOI: 10.1002/jpen.1067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Contrast Administration on Computed Tomography–Based Analysis of Visceral Adipose and Skeletal Muscle Tissue in Clear Cell Renal Cell Carcinoma

Abstract: Future analyses should consider the phase of contrast during CT imaging because it may alter the interpretations of several parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
4
39
0
1
Order By: Relevance
“…Cross sectional areas of these tissues were quantified by summing up tissue pixels and multiplying by the pixel surface areas. Given the effect of contrast medium administration on muscle and VAT cross-sectional area and radiodensity estimation [29], only CT slices without contrast were selected for body composition analysis in this study. Using non-contrast abdominal CT images, high intraobserver and interobserver reproducibility was observed in measuring the body composition parameters in clinical populations [29].…”
Section: Ct Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cross sectional areas of these tissues were quantified by summing up tissue pixels and multiplying by the pixel surface areas. Given the effect of contrast medium administration on muscle and VAT cross-sectional area and radiodensity estimation [29], only CT slices without contrast were selected for body composition analysis in this study. Using non-contrast abdominal CT images, high intraobserver and interobserver reproducibility was observed in measuring the body composition parameters in clinical populations [29].…”
Section: Ct Image Analysismentioning
confidence: 99%
“…Given the effect of contrast medium administration on muscle and VAT cross-sectional area and radiodensity estimation [29], only CT slices without contrast were selected for body composition analysis in this study. Using non-contrast abdominal CT images, high intraobserver and interobserver reproducibility was observed in measuring the body composition parameters in clinical populations [29]. Using software such as Slice-O-Matic, tissues were selected semi-automatically and the average time to quantify body composition parameters was found to be around eight minutes, which can be easily carried out by any trained observers with a knowledge of human anatomy [30].…”
Section: Ct Image Analysismentioning
confidence: 99%
“…The slight increase of SMA and SMI may be attributed to the contrast agent, which increases the attenuation values of muscle fibers that were below the defined threshold on unenhanced images . Several previous studies showed similar results, and the increase in SMI does not alter the identification of patients with low SMI . Thus, CT‐based assessment of SMI is an easy and reliable method independent of contrast enhancement.…”
Section: Discussionmentioning
confidence: 73%
“…However, the time points of contrast enhancement and study cohort in our study were different from theirs. Paris et al also revealed that the increase in MRA with contrast‐enhancement phases altered the identification of individuals with low MRA. Hence, the definition of the skeletal muscle measures should be standardized to a particular phase to ensure their applicability and comparability, especially for MRA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation